Social financial information security risk analysis and prevention - Jian-ming ZHU; Bo GAO (网络与信息安全学报)
The finance is reforming deeply in the country now, and the internet finance develops quickly under the background of “internet+”. Especially with the rapid development of mobile internet and internet socialization, the social finance has become a trend. But at the same time, it faces information security risk brought by the social network and the mobile internet that are the bases of social finance. The social financial potential information security risks were introduced. By modeling a social finance security game, that the correct defense strategy and adopt effective defense measures should be developed was analyzed and pointed out to cope with the social finance information security risks, so as to promote the healthy and quick development of social finance in our country.